Note—On “Optimizing Field Repair Kits Based on Job Completion Rate” - March, Salvatore T.; Scudder, Gary D. (Management Science, 1984)
In a recent paper, Mamer and Smith (Mamer, J. W., S. A. Smith. 1982. Optimizing field repair kits based on job completion rate. Management Sci. 28 (11) 1328–1333.) presented a formulation for determining the optimal kit of parts and tools for on-site equipment repairs under a job completion criterion. The optimal kit minimizes the sum of expected broken job costs plus the annual inventory holding cost for those parts stocked. A broken job occurs whenever a repair cannot be completed because one or more of its required parts are not included in the field repair kit. Assuming equal penalties for all broken jobs, an algorithm developed by Eisner and Severance (Eisner, M. J., D. G. Severance. 1976. Mathematical techniques for efficient record segmentation in large shared databases. J. Assoc. Comput. Mach. 23 (4) 619–635.) in a different context can be used to determine a set of optimal policies and a range on the penalty cost for which each policy is optimal. The ranges cover all penalty costs from 0 to ∞. This is significant for the repair kit problem since the actual penalty cost of broken jobs may be difficult to determine exactly.